How Is The Readiness To Carry Out Online Registration In The Malang Primary Health Care? - Hartaty Sarma Sangkot; Endang Sri Dewi Hastuti Suryandari; Avid Wijaya (Poltekkes Kemenkes Surakarta, 2022)
Background: RME is one of the information subsystems connected to other information subsystems in the health service facility, such as patient registration activities. The purpose of this study is to evaluate the readiness of PHC in Malang to use online registration applications. Methods: Quantitative descriptive research was used. The research was conducted in 15 PHCs in Malang in June 2021. The population in this study were all patients, all heads of PHCs, and all Medical Record Officers (MRO) at PHCs. The respondents were 15 physicians, 27 MRO, and 330 patients from 15 PHCs seeking medication. The data was measured using a questionnaire designed for patient groups and healthcare provider groups in PHCs per the available literature. Additionally, the scalability and repeatability coefficients for the survey questions are employed in the validity test. The response to questions was presented as an average value. Results: In accordance with the average Likert Scale, the Head of PHC (4,2), MRO (4,15), and patients (4,18) were all ready to use online registration. The study's findings about PHC revealed that 100% of PHC in Malang had adequate human resources, an effective operating system and application, a supporting computer, and a budget. Only around 50% of PHCs have an online registration policy, though. Conclusion: All PHCs and patients were ready to use online registration. According to this study, all PHCs should be ready to prepare facilities and infrastructure and implement online registration.